FIGURATIVE LANGUAGE IN LOVE expressionS:A STUDY BASED ON THE ALBUM ENTITLED "PURE" - Nisa Fatihah, - (2011)
This research paper is entitled Figurative Language in Love expressions: A Study Based on The Album Entitled "Pure". In this paper, the study investigated two research questions: 1) What types of figurative languages presented in "Pure" album? 2) What are dominant figurative languages presented in "Pure" album? The study applied descriptive qualitative method to analyze all the selected samples in order to classify and explain them. The result of the research indicated that there were 17 types of figurative language found in the song lyrics. Those were 102 figurative language which comprise rhetorical schemes and rhetorical tropes. Rhetorical schemes contained types of figurative language such as alliteration (2 items), assonance (3 items), anadiplosis (2 items), anaphora (10 items), epistrophe (3 items), epizeuxis (19 items), erotesis (11 items), symploche (4 items) and polysyndeton (1 item). Meanwhile, rhetorical tropes contained types of figurative language such as hyperbole (12 items), irony (2 items), metaphor (2 items), metonymy (19 items), paradox (4 items), personification (1 item), simile (4 items) and synecdoche (3 items). From the group of rhetorical schemes, epizeuxis was the most dominant figurative language found in the song lyrics. Meanwhile, from the group of rhetorical tropes, metonymy was the most dominant figurative language found in the song lyrics.